Algorithmic Gossiping: sharing and non-sharing that evolve algorithmic imaginaries to folk theories - Gaohui Cao; Zhang Wen; Puyi Liu (Information Research: An International Electronic Journal)
Introduction. This paper presents a work-in-progress diary study exploring how algorithmic gossiping contributes to the transformation of individual, momentary algorithmic imaginaries into shared and consolidated folk theories.